Suppression of MRPL23 induces cellular senescence in hepatocellular carcinoma by targeting HMGB1 - Ya-Bin Huang; Shi-meng Xu; Min Li; Jin Chen; Cui-Hua Lu; Qing-qing Liu (Discover Oncology)
Abstract Hepatocellular carcinoma (HCC) is the most common form of liver cancer and remains a global health challenge. The biological process of HCC is very complex, involving the imbalance of tumor suppressor genes and oncogenes, abnormal activation of molecular signaling pathways, and the differentiation of HCC cells. Standard clinical approaches for HCC treatment encompass surgery, chemotherapy, and radiation therapy. However, treatment options for advanced HCC are constrained, primarily due to an incomplete understanding of its underlying mechanisms. Cellular senescence is a crucial mechanism that influences the pathophysiological processes of HCC and serves as a potent barrier to tumor development. Our research identified the biological functions and mechanisms of Mitochondrial Ribosomal Protein L23 (MRPL23) in relation to cellular senescence in HCC. Results demonstrated that MRPL23 was upregulated in both tumor tissues and hepatoma cells. Additionally, the inhibition of MRPL23 resulted in decreased cell proliferation and promoted cellular senescence. Moreover, MRPL23 deficiency protected against HCC progression in a mouse model. Finally, we confirmed that MRPL23 regulated cellular senescence by targeting HMGB1 using the inhibitor NecroX-7. These findings laid the foundation for developing potential therapies for HCC by inhibiting MRPL23 or inducing senescence.